2010
DOI: 10.1074/jbc.m110.113555
|View full text |Cite
|
Sign up to set email alerts
|

The LAMMER Kinase Homolog, Lkh1, Regulates Tup Transcriptional Repressors through Phosphorylation in Schizosaccharomyces pombe

Abstract: Disruption of the fission yeast LAMMER kinase, Lkh1, gene resulted in diverse phenotypes, including adhesive filamentous growth and oxidative stress sensitivity, but an exact cellular function had not been assigned to Lkh1. Through an in vitro pull-down approach, a transcriptional repressor, Tup12, was identified as an Lkh1 binding partner. Interactions between Lkh1 and Tup11 or Tup12 were confirmed by in vitro and in vivo binding assays. Tup proteins were phosphorylated by Lkh1 in a LAMMER motif-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…The fission yeast LAMMER kinase homolog, Lkh1, regulates Tup transcriptional repressors through phosphorylation, and an lkh1 null mutant flocculates upon reaching stationary phase in liquid media and adheres to agar surfaces (15). In addition, we previously isolated a fission yeast gsf1 mutant that flocculates constitutively during growth in liquid media and also adheres to agar (20,37).…”
Section: Resultsmentioning
confidence: 99%
“…The fission yeast LAMMER kinase homolog, Lkh1, regulates Tup transcriptional repressors through phosphorylation, and an lkh1 null mutant flocculates upon reaching stationary phase in liquid media and adheres to agar surfaces (15). In addition, we previously isolated a fission yeast gsf1 mutant that flocculates constitutively during growth in liquid media and also adheres to agar (20,37).…”
Section: Resultsmentioning
confidence: 99%
“…Lkh1 encodes a LAMMER kinase homolog, which represses expression of adhesions (12). Kang et al (2010) also showed that deletion of the tup12 ϩ gene, functioning as a Lkh1 binding partner, resulted in a nonsexual flocculation in the fission yeast (13). Recently, Matsuzawa et al (2011) reported that overexpression of FLO8, encoding a transcriptional activator of the dominant flocculation genes in budding yeast Saccharomyces cerevisiae, induced a nonsexual flocculation in fission yeast (14).…”
mentioning
confidence: 99%
“…It is also possible that co-repressor activity can be altered through post-translational modifications such as phosphorylation and sumoylation. While these modifications affect the binding properties of Gro/Tup1 proteins in animals and fungi, [61][62][63][64] it is presently not clear whether such mechanisms are also used to control plant co-repressor activity.…”
Section: Resultsmentioning
confidence: 99%